PERAN LEMBAGA PENDIDIKAN AL- QUR'AN JABAL IKHWAN DALAM MENGATASI BUTA AKSARA AL- QUR'AN BAGI MASYARAKAT DI DESA GUNUNG LANANG TEGALREJO BAYAT KLATEN TAHUN 2023 - Hidayah, Nur; Suhadi, S; Sulistyowati, S (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
The purpose of this study was to determine the role of the Jabal Ikhwan Al- Qur’an Education Institute Gunung Lanang Tegalrejo Bayat Klaten. The approach used in this research is qualitative. Data analysis was used to reduce data, present, and verify data. The results of this study indicate that the role of Jabal Ikhwan Qur’anic Education Institution in combating Qur'anic illiteracy for the community of Gunung Lanang Tegalrejo Bayat Klaten Village is teaching the Qur'an to the community and supporting agents of change. The supporting factors are: hope, encouragement and wise advice from the managers of the Jabal Ikhwan Qur'anic education institution so that they are enthusiastic about learning to read the Qur'an. As for the factors that hinder the eradication of illiteracy and Quranic illiteracy for the community of Gunung Lanang Tegalrejo Bayat Klaten are the lack of self-confidence, the environment of learners or the community. lack of self-confidence, unfavourable environment for learners or the community and lack of support from local authorities.